Analisis Pengaruh Kompetensi Sumber Daya Manusia Dan Kompensasi Terhadap Kinerja Karyarwan PT. Indonesia Royal Paper - Rosidi, Imron; Syahrinullah, Syahrinullah (Journal of Management Branding, 2024)
The study aims to determine the effect of human resource competence and compensation on employee performance at PT Indonesia Royal Paper. The research uses quantitative methods with multiple linear regression approaches. The data obtained is primary data obtained from distributing questionnaires with a Likert scale to the object of research. The sample was selected using purposive sampling technique with a total of 39 respondents and the data was analysed using multiple linear regression analysis with the help of SPSS software version 26. The results of this study indicate that the human resource competency variable has a significant effect on employee performance at PT Indonesia Royal Paper, the compensation variable has no significant effect on employee performance at PT Indonesia Royal Paper, and Human Resource Competencies and Compensation simultaneously have a significant effect on Employee Performance at PT Indonesia Royal Paper